PENERAPAN MODEL PAKEM (PEMBELAJARAN AKTIF, KREATIF, EFEKTIF DAN MENYENANGKAN) UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT TOPENG PADA SISWA KELAS V SDN I69 PEKANBARU - Mulyani '; Zariul Antosa; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is motivated by the low skills of the students in making the mask. Among students who totaled 28 people only 5 students were categorized skilled. This study is a Classroom Action Research (CAR) conducted aims to improve the skills of making masks Elementary School fifth grade students 169 Pekanbaru to implement PAKEM strategy. Data collection instruments in this thesis is the teacher and student activity sheets and sheets of skills membat mask. This thesis presents that the implementation of active and creative learning strategies can increase the skill of creating masks Elementary School fifth grade students 169 Pekanbaru. It can be seen from the results of the skills assessment made masks at baseline with an average value of 60.07 has increased in the first cycle in order to obtain an average value of 67.92, an increase in the second cycle in order to obtain an average value of 77.74 , Teacher activity namely on the activity of the first cycle of the first meeting of teachers with a value of 50 increased in the first cycle a second meeting with the increased value of 70.83 and also in the second cycle the first meeting with a value of 91.67, at the second meeting of the second cycle increased again to 95.83. Overall activity of teachers has increased from cycle I and cycle II. The increase in the student activity which is the activity of the first cycle students first meeting with a percentage of 62.5% increase in the first cycle a second meeting with a percentage of 79.33%. And increased also in cycle IIpertemuan pertamadengan percentage 83.33%, in the second meeting of the second cycle occurred again increased to 95.83. Overall activity of students has increased from cycle I and cycle II. Results of the study in class V SDN 169 Pekanbaru prove that the application of PAKEM strategy can improve the skills of making masks fifth grade students of SDN 169 Pekanbaru.Keywords : PAKEM, the skills to make a mask2